Porous Bilayer Electrode‐Guided Gas Diffusion for Enhanced CO2 Electrochemical Reduction. Issue 11 (4th November 2021) - Wang, Yucheng; Lei, Hanhui; Xiang, Hang; Fu, Yongqing; Xu, Chenxi; Jiang, Yinzhu; Xu, Ben Bin; Yu, Eileen Hao; Gao, Chao; Liu, Terence Xiaoteng
Abstract : Graphene Aerogels In article number 2100083 by Ben Bin Xu, Eileen Hao Yu, Chao Gao, Terence Xiaoteng Liu, and coworkers, an advanced structured graphene aerogel–carbon paper hybrid gas diffusion electrode reaction cell offers directional diffusion of gas molecules onto the catalyst bed. The described porous bilayer configuration enables unique CO2 mass transfer features with the enhanced Faradaic efficiency of carbonaceous products over 94%, suppressing the hydrogen evolution reaction and considerable durability as a result of electrolyte permeation prevention.